Hubungan Kekuatan Otot Bahu Dan Reaksi Tangan Terhadap Kecepatan Pukulan Straight Pada Olahraga Tinju Di Sasana Kota Baru Jambi - Fransiskus Sinaga; Alek Oktadinata; Anggel Hardiyanto (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Indonesia as a country of law has regulations that govern various aspects of life, including sports, as stipulated in Law No. 11 of 2022. Sports are not only physical activities but also social phenomena that play a role in improving the health, fitness, and achievements of the nation. One of the sports that has high popularity is boxing, which requires not only technical skills but also prime physical condition. In boxing, an effective punch requires a combination of various factors, especially shoulder muscle strength, hand reaction, and speed. Straight punches, as one of the basic techniques in boxing, play an important role in attack strategy. This technique requires optimal coordination between the shoulder and hand muscles to produce fast, strong, and accurate punches. In addition, fast hand reactions allow boxers to attack and defend efficiently, while speed is the main factor in determining the success of an attack. The relationship between shoulder muscle strength, hand reaction, and punch speed is very significant in determining a boxer's performance. Therefore, these three aspects must be developed optimally to improve fighting skills and chances of winning in competitions. Thus, this study highlights the importance of integrating physical training that focuses on strength, speed, and reaction in the development of boxing athletes.